2018
DOI: 10.1016/j.acap.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Parents Who Decline HPV Vaccination: Who Later Accepts and Why?

Abstract: Our findings suggest secondary acceptance of HPV vaccination is common, with more than two-thirds of parents in this national sample accepting or intending to accept HPV vaccination after declination. Providers should seek to motivate secondary acceptance by delivering repeated, high-quality recommendations for HPV vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
80
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 27 publications
(35 reference statements)
3
80
1
5
Order By: Relevance
“…c Intensity of Treatment Rating Scale, Version 3.0. 32 Yet, in a study of subspecialty providers, approximately half of providers reported that they do not routinely recommend the HPV vaccine to their patients with chronic illness. Importantly, survivors who reported vaccine intent at the survey were 4 times more likely to subsequently initiate the vaccine during the follow-up period in comparison with those not reporting intent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c Intensity of Treatment Rating Scale, Version 3.0. 32 Yet, in a study of subspecialty providers, approximately half of providers reported that they do not routinely recommend the HPV vaccine to their patients with chronic illness. Importantly, survivors who reported vaccine intent at the survey were 4 times more likely to subsequently initiate the vaccine during the follow-up period in comparison with those not reporting intent.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, provider recommendation has been shown to be related to secondary acceptance of the HPV vaccine among parents who initially decline the HPV vaccine for their adolescent child. 32 Yet, in a study of subspecialty providers, approximately half of providers reported that they do not routinely recommend the HPV vaccine to their patients with chronic illness. 33 In this study of cancer survivors, only 24% of vaccine-naive survivors reported receiving a provider recommendation for the HPV vaccine, and this suggests the need for subspecialty providers, including oncologists, to promote and facilitate HPV vaccine uptake in adolescent and young adult cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,30 In a survey of family practitioners and pediatricians, 35% always recommended HPVV to their patients aged 11 to 12 years, whereas 50% did so to patients aged 18 to 26 years. 35,40 Furthermore, a recent study found that parents viewed cancer prevention as the most persuasive reason for vaccinating their children, and such information could be incorporated into provider communication strategies and parental educational materials targeting unvaccinated adoloscents. 27,31 Parents most commonly identify a lack of provider recommendations, awareness, and knowledge as reasons for not vaccinating their children, and younger adolescent age is also related to parental refusal and delay of HPVV.…”
Section: Discussionmentioning
confidence: 99%
“…39 In addition, parental text-message and mailed reminders as well as in-clinic provider electronic reminders may boost vaccination rates, and repeated physician recommendations may be needed to convince parents who initially refuse. 35,40 Furthermore, a recent study found that parents viewed cancer prevention as the most persuasive reason for vaccinating their children, and such information could be incorporated into provider communication strategies and parental educational materials targeting unvaccinated adoloscents. 41 Other countries, including Portugal, England, and Australia, have achieved HPVV initiation rates of 80% or higher with large-scale and population-based approaches, including school-based programs.…”
Section: Discussionmentioning
confidence: 99%
“…Chhabra et al 5 use a health literacy framework (readability, suitability, and comprehensiveness of content) to evaluate 38 HPV counseling materials; although many materials scored low for readability, a qualitative review of 4 products by parents showed that the documents were influential in convincing them to vaccinate. The final article in this section, by Kornides et al, 6 summarizes the results of a survey of parents who initially refused the HPV vaccine for their child—45% reported accepting the vaccine on subsequent visits with their health care provider, showing the importance of repeatedly discussing HPV vaccination with patients even if parents initially decline the vaccine.…”
mentioning
confidence: 99%